The green sin: How exchange rate volatility and financial openness affect green premia - Alessandro Moro; Andrea Zaghini (Goethe University Frankfurt, Center for Financial Studies (CFS), 2023)
We propose a model with mean-variance foreign investors who exhibit a convex disutility associated to brown bond holdings. The model predicts that bond green premia should be smaller in economies with a closer financial account and highly volatile exchange rates. This happens because foreign intermediaries invest relatively less in such economies, and this lowers the marginal disutility of investing in polluting activities. We find strong empirical evidence in favor of this hypothesis using a global bond market dataset. Exchange rate volatility and financial account openness are thus able to explain the higher financing costs of green projects in emerging markets relative to advanced economies, especially when green bonds are denominated in local currency: a disadvantage that we can call the "green sin" of emerging economies.
Keywords: F21; F30; F31; G11; G12; 330; Green bonds; Greenium; Exchange rate volatility; Financial openness; Original sin